Rethinking Guest Experience Drivers in Hospitality: A Guest-Centered Perceived Asset Performance Model - Siti Yulia Irani Nugraha; Eko Susanto; Sri Utari Widyastuti; Siti Hafsah Zulkarnain (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2026)
This study investigates how contemporary experience drivers—digital guest experience, sustainability perception, brand authenticity, and service personalization—shape perceived asset performance and customer loyalty in the Indonesian hospitality context. Using data collected from 367 hotel guests across Indonesia, the research develops and tests an integrated structural model grounded in Experience Economy Theory, Service-Dominant Logic, and Customer Engagement Theory. While prior literature often assumes that all experience drivers uniformly enhance guest value, this study reveals a more nuanced mechanism: some drivers (e.g., authenticity, personalization) directly influence experiential value, while others (notably digital guest experience) primarily drive customer engagement. The findings identify experiential value and customer engagement as critical mediators that link experience design to perceived asset performance. Specifically, the study demonstrates that guest engagement is essential for converting technological features into favorable asset evaluations. By shifting the focus from traditional financial metrics to guest-centered perceived asset performance, this research emphasizes the psychological and emotional dimensions of hospitality value. Theoretical contributions include clarifying differentiated experience pathways and empirically validating a guest-centric model of asset performance. For practitioners, the results highlight the need to align digital innovation with emotionally resonant service strategies to foster loyalty in emerging hospitality markets like Indonesia.